Fomo dan Perilaku Komunal: Dampak Psikologi Komunikasi Massa di Media Sosial - Amalia, Aulia; Riya, Riya; Fatmah, Nor; Faisal, Ijang; Origenes, Ritchelle W. (Yayasan Cendekia Gagayunan Indonesia, 2025)
Social media has become a space for gathering and socializing horizontally and vertically, enabling direct and simultaneous communication. However, with increasing use, a social psychology issue has emerged: FOMO (Fear of Missing Out), or the fear of missing out on information. FOMO encourages individuals to behave as if they are part of something bigger, even if they are not actively involved. This phenomenon impacts mental health and communication styles in a digital society. This study examines the impact of FOMO and communal behavior on the psychology of mass communication on social media, particularly among millennials and Generation Z. The method used was a literature review, referencing recent journals and scientific articles. The results indicate that social conditions acquired through social media are directly related to increased FOMO. Therefore, effective communication and digital literacy are crucial for managing social media use to minimize the negative impacts of FOMO while maintaining healthy social interactions. These findings emphasize the need for user awareness and greater discretion in using social media to support mental well-being and quality communication in a digital society.